Molecular characterization and genetic structure of the local criollo pig breeds (Sus scrofa domestica) from Ecuador, using microsatellite markers - Julio César Vargas Burgos; Francisco Jesús Velásquez Rodriguez; Edilberto Chacón Marcheco (Acta Agronómica)
The molecular markers have shown their great utility in the characterization of the domestic animals, hence, the objective of this work was to characterize, genetically, the Creole pig of Ecuador by means of microsatellites. Samples of hair of 15 animals were gathered. A panel of 25 microsatellites, the amplification of the same was carried out by means of the reaction in chain of the polymerase and the amplified fragments, separated by electrophoresis in gels of polyacrylamide. In addition, were calculated the half number of alleles by locus (MNA), the allelic frequencies, the expected (He) and the observed (Ho) heterozygosity , the content of polymorphic information (PIC), as well as the balance Hardy-Weinberg (EHW) and the FIS for marker. The half number of alleles found by locus has been of 6.2 and the percentage of individual heterozygote behaved above of 60%. Of the entirety of the studied loci the 68% showed a high PIC. These results show that the Ecuadorian Creole pig possesses a high genetic diversity, essential information to optimize the national strategies of conservation and it improvement of this genotype in Ecuador.